Lack of mitochondrial ferritin aggravated neurological deficits via enhancing oxidative stress in a traumatic brain injury murine model. Issue 6 (6th November 2017) - Wang, Ligang; Wang, Libo; Dai, Zhibo; Wu, Pei; Shi, Huaizhang; Zhao, Shiguang
Abstract : Oxidative stress has been strongly implicated in the pathogenesis of traumatic brain injury (TBI). Mitochondrial ferritin (Ftmt) is reported to be closely related to oxidative stress. However, whether Ftmt is involved in TBI-induced oxidative stress and neurological deficits remains unknown. In the present study, the controlled cortical impact model was established in wild-type and Ftmt knockout mice as a TBI model. The Ftmt expression, oxidative stress, neurological deficits, and brain injury were measured. We found that Ftmt expression was gradually decreased from 3 to 14 days post-TBI, while oxidative stress was gradually increased, as evidenced by reduced GSH and superoxide dismutase levels and elevated malondialdehyde and nitric oxide levels. Interestingly, the extent of reduced Ftmt expression in the brain was linearly correlated with oxidative stress. Knockout of Ftmt significantly exacerbated TBI-induced oxidative stress, intracerebral hemorrhage, brain infarction, edema, neurological severity score, memory impairment, and neurological deficits. However, all these effects in Ftmt knockout mice were markedly mitigated by pharmacological inhibition of oxidative stress using an antioxidant, N-acetylcysteine. Taken together, these results reveal an important correlation between Ftmt and oxidative stress after TBI. Ftmt deficiency aggravates TBI-induced brain injuries and neurological deficits, which at least partially through increasing oxidative stress levels. Our data suggest that Ftmt may be a promising molecular target for the treatment of TBI.